International indebtedness and the developing countries - Abbott, George C. (London : Croom Helm ; White Plains, N.Y. : M. E. Sharpe, 1979)
This book provides an informative review of the implications of the rapid growth in external debt by the developing countries. Steadily claiming a greater proportion of limited export earnings, the burden of the service payments is straining the external positions of these countries and reducing the resources available for development. Reflecting the current concern in the international community, the continued growth in the level of external debt has heightened the probability of default and forced retrenchment of development plans. As a means of avoiding this outcome, the author proposes a debt-relief-aid scheme that is aimed at alleviating the burden of these service payments while at the same time, maintaining a continued transfer of resources to the developing countries.
Includes index.
Bibliography: p. 304-307.
usc 20/08/18
Loans
Keywords: Debts, External; Developing countries